Self-reported determinants for subjective financial distress: a qualitative interview study with German cancer patients - Züger, Andrea; Mathies, Viktoria; Mehlis, Katja; Pauge, Sophie; Richter, Luise; Surmann, Bastian; Ernst, Thomas; Menold, Natalja; Greiner, Wolfgang; Winkler, Eva C. (BMJ open, 2025)
Objectives Patient-reported financial effects of a tumour disease in a universal healthcare setting are a multidimensional phenomenon. Actual and anticipated objective financial burden caused by direct medical and non-medical costs as well as indirect costs such as loss of income can lead to subjective financial distress. To better understand subjective financial distress, the presented study explores self-reported determinants for subjective financial distress in German patients with cancer, aiming to inform a new German-language patient-reported outcome measure for determining the financial effects of a tumour disease. - Design Semistructured interviews with n=18 patients with cancer were conducted between May 2021 and December 2021. Patients were recruited based on a purposive sampling strategy in outpatient and inpatient settings. The interviews were audiorecorded, transcribed verbatim and analysed using qualitative content analysis. - Setting Participants were recruited from two German academic cancer centres, that is, the National Center for Tumor Diseases Heidelberg and Jena University Hospital. - Participants 18 patients who had undergone cancer-related therapy for at least 2 months were interviewed (10 females). - Results Based on the results of the qualitative content analysis, we developed a multicomponent construct of determinants that could influence subjective financial distress. The self-reported determinants can be classified into material (savings, good salary, shared rent through shared living, employed partner, paid-off house, potential financial support from family and friends, work-related specifics, consumer restrictions, out-of-pocket-costs and anticipated financial changes), social (social support from friends and family), systemic (administrative hurdlers and insurance cover) and inner personal determinants (coping strategies, change of attitude, character traits). - Conclusion Subjective financial distress depends not only on material but also on social, systemic and inner personal determinants. Knowledge of these determinants can inform a new comprehensive German-language instrument for measuring self-reported financial effects of a tumour disease. - Trial registration number NCT05319925.